2016
DOI: 10.1007/s13201-016-0416-1
|View full text |Cite
|
Sign up to set email alerts
|

Management of a water distribution network by coupling GIS and hydraulic modeling: a case study of Chetouane in Algeria

Abstract: For more effective management of water distribution network in an arid region, Mapinfo GIS (8.0) software was coupled with a hydraulic model (EPANET 2.0) and applied to a case study region, Chetouane, situated in the north-west of Algeria. The area is characterized not only by water scarcity but also by poor water management practices. The results showed that a combination of GIS and modeling permits network operators to better analyze malfunctions with a resulting more rapid response as well as facilitating i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…ArcCatalog and ArcGIS can be used as network design and analysis tools [132]. The network, designed in ArcCatalog, holds benefits in designing and implementing sewerage systems [133,134], analyzing and monitoring such systems [135,136], and simulating like that of urban sewerage flow volume [137,138]. Reference [139] marks the significant role of monitoring and controlling systems in water supply and sewerage facilities.…”
Section: Utilitiesmentioning
confidence: 99%
“…ArcCatalog and ArcGIS can be used as network design and analysis tools [132]. The network, designed in ArcCatalog, holds benefits in designing and implementing sewerage systems [133,134], analyzing and monitoring such systems [135,136], and simulating like that of urban sewerage flow volume [137,138]. Reference [139] marks the significant role of monitoring and controlling systems in water supply and sewerage facilities.…”
Section: Utilitiesmentioning
confidence: 99%
“…The methodology adopted was based, first, on the construction of a cartographic database. Secondly, a conceptual model of the surface water mobilization system is developed using the WEAP software (Abdelbaki et al 2017). The third step was to establish relationships between the nodes of the conceptual model with the database.…”
Section: Input Datamentioning
confidence: 99%
“…Venkata Ramana & Sudheer Chekka (2018) suggested that whenever demand for water exceeds the supply by a larger amount, there is no other way but to overhaul the whole network with the replacement of pipes with bigger diameter pipes and providing extra storage tanks for continuous water supply. Abdelbaki et al (2017) combined GIS and EPANET for effective water supply distribution modeling for Chetouane, Algeria, which is characterized by water scarcity and poor water management practices. They concluded that combining GIS with WDS modeling allows for better analysis, diagnosis of problems, improved management and understanding of a WDS along with prediction of the future situation, which assists greatly in making decisions that are more informed and ensures optimum levels of satisfaction from the consumer side for WDS operation.…”
Section: Introductionmentioning
confidence: 99%